Performance Comparison of AHRS Algorithm for Quad Copter Application - Jie, Min-Seok; Kim, Da-Un; Choi, Won-Hyuck (International Journal of Engineering and Technology, 2019)
An Inertial Measurement nit (IMU) is an internal component of a device such as an unmanned aircraft, airplane, or satellite. Use an accelerometer, a gyro scope, and a ground magnetic meter to measure acceleration and torque. It's an integrated device that allows us to measure movement in three-dimensional space. In recent years when there are problems with receiving GPS signals from tunnels, indoors or electromagnetic interference, technologies such as navigation and others are being used to estimate locations such as IMU information. Accuracy and quick response are the most important requirements for all systems mentioned. Therefore, this paper compared the accuracy of the quaternion algorithm with the calculation speed based on the gradient descent method among the different solutions. The experiment used a quad cover to verify the estimated accuracy.Â Â